Magnetic high-resilience IXPE foam material for buffer gasket and preparation method of magnetic high-resilience IXPE foam material

By introducing silane-coupled magnetic iron oxide powder and alkyl lignin in the polyethylene foam material, and using electron radiation crosslinking and high-temperature foaming technology, the problem of insufficient mechanical properties of polyethylene foam material is solved, and an IXPE foam material with high resilience and strong magnetic induction is prepared.

CN119570139APending Publication Date: 2025-03-07ZHEJIANG WANLI NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411875329.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing polyethylene foam materials have poor mechanical properties during buffer fixation and cannot meet the needs of high rebound fitting.

Method used

By introducing magnetic iron oxide powder and alkyl lignin treated with silane coupling, combined with electron irradiation crosslinking and high-temperature foaming technology, magnetic high rebound IXPE foam material was prepared.

Benefits of technology

It significantly improves the magnetic and mechanical properties of the material and improves the performance in mechanical shock absorption and buffering. The product has high rebound resistance, high magnetic induction strength and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure ANTKCCTGX7KTX30LI3WRI6VRKQJWSZ6JQVGOXK2Y
    Figure ANTKCCTGX7KTX30LI3WRI6VRKQJWSZ6JQVGOXK2Y
  • Figure IKDOPKLH7CXT4Z7CZYZFKOAVMVTVNUVCTSVSXUV5
    Figure IKDOPKLH7CXT4Z7CZYZFKOAVMVTVNUVCTSVSXUV5
  • Figure MYS8MHPASEP5EEOSOJEDWKTDFNOFW68DUZUCIHHS
    Figure MYS8MHPASEP5EEOSOJEDWKTDFNOFW68DUZUCIHHS
Patent Text Reader

Abstract

The invention discloses a magnetic high-resilience IXPE foam material for a buffer gasket and a preparation method of the magnetic high-resilience IXPE foam material. According to the method, a magnetic component and an alkyl functionalized lignin functional component are added, and a magnetic material is subjected to silane coupling treatment, so that the compatibility of the magnetic material and polyolefin is improved, the length and the number of alkyl chains are adjusted, the alkyl functionalized lignin is promoted to be connected into a polyethylene network, and the mechanical property of a product is improved; the product is endowed with magnetism on the basis of ensuring the high resilience of the product. The product has the advantages of high rebound resilience, magnetism and residual magnetic induction intensity gt; when the thickness is 0.1 T, the apparent density is smaller than 0.1 g / cm < 3 >, the thickness is 1 mm, the tensile strength is 1.5 MPa or above, and the elongation is 200% or above; raw materials are rich in source and low in price; and the prepared material has the advantages of wide application and the like in the mechanical damping cushion gasket industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a magnetic high-resilience IXPE foam material for a buffer gasket and a preparation method thereof. Background Art

[0002] Radiation cross-linked polyethylene foam is a new type of foamed plastic with a closed-cell structure between soft (polyurethane) and hard (polystyrene) foam plastics. It has a series of properties such as superior strength, toughness, elasticity, flexibility, wear resistance, chemical corrosion resistance, low temperature resistance and good insulation. It can be used as a good insulating, heat-insulating, shock-proof and buoyancy material, and is widely used in various fields such as industry, agriculture, construction and transportation.

[0003] The product used as a buffer gasket is fitted in the appropriate position. During the fastening process, the gasket needs to be effectively adsorbed on the surface of the metal material. Therefore, the magnetism of the product can ensure its good fit. Since polyethylene has more long chain branches, larger molecular distances, poor mechanical properties, higher crystallinity, and weaker molecular chain flexibility, it cannot meet the requirements of high rebound fit during the buffering and fixing process. In response to the above problems, a solution is proposed below. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a magnetic high-resilience IXPE foam material for a buffer gasket, thereby improving the magnetic and mechanical properties of the prepared product and greatly improving the performance of the product in terms of mechanical shock absorption and buffering.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions: A magnetic high-resilience IXPE foam material for a buffer gasket, characterized by comprising the following weight components: 35-60 parts of polyethylene; 10-30 parts of alkyl lignin; 8-15 parts of magnetic iron oxide powder; 10-30 parts of elastomer; 1 to 5 parts of sensitizer; 2 to 20 parts of azodicarbonamide foaming agent; 0.5-4 parts of antioxidants; The polyethylene is low-density polyethylene, and the magnetic iron oxide powder is magnetic iron oxide powder that has been treated with silane coupling. After the components are mixed, they are added into a screw extruder for mixing and extrusion to obtain a mother sheet, and the mother sheet is cross-linked by electron radiation. After the electron radiation cross-linking is completed, the obtained material is subjected to high-temperature foaming treatment to obtain a magnetic high-resilience IXPE foam material.

[0006] Preferably, the polyethylene is General low-density polyethylene with a density of 0.901~0.922g / cm3 and a melt index of 1~6 g / 10 min, Linear low-density polyethylene with a density of 0.905~0.930g / cm3 and a melt index of 0.3~5g / 10 min, One or more ultra-low density polyethylenes with a density of 0.880-0.910 g / cm3 and a melt index of 0.35 g / 10 min.

[0007] Preferably, the elastomer is one or more of EPDM rubber, ethylene-octene copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, natural rubber, isobutylene rubber, styrene-butadiene rubber, styrene-butadiene block copolymer, and pentylbenzene block copolymer.

[0008] Preferably, the antioxidant is Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 1,1,3-Tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-Trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, Any one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, and tert-butylhydroquinone.

[0009] Preferably, the sensitizer is one or more of zinc stearate and zinc oxide.

[0010] A method for preparing a magnetic high-resilience IXPE foam material for a cushioning gasket, using magnetic iron oxide powder and alkyl lignin as reinforcing components to prepare a magnetic high-resilience polyethylene foam material, specifically comprising the following steps: S1: synthetic magnetic iron oxide powder, The magnetic iron oxide, silane coupling agent and toluene are heated to 80-120° C. in a mass ratio of 100:1-10:1000, reacted for 4-24 hours, filtered, washed and dried to obtain magnetic iron oxide powder; S2: Synthetic alkyl lignin, Lignin with a molecular weight of less than 5000, olefinic acid chloride and N,N-dimethylformamide are mixed and stirred in a mass ratio of 100:10-50:100-500, nitrogen is introduced to replace the air, and then heated at 100-150° C., reacted for 4-12 hours, filtered, washed with ethyl acetate and dried to obtain alkyl lignin; S3: preparing polyethylene foam, Magnetic iron oxide powder, alkyl lignin, polyethylene, elastomer, antioxidant, azodicarbonamide foaming agent, sensitizer, etc. are uniformly mixed in a mass ratio of 8-15:10-30:35-60:10-30:0.5-4:2-20:1-5, and then added into a single screw extruder for extrusion at an extrusion temperature of 95-130°C, a screw speed of 6-25rpm, and a die head temperature of 90-130°C to obtain a mother sheet with a certain thickness; The master sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 5 to 50 kGy to form a cross-linked polymer network to obtain a cross-linked master sheet; The cross-linked mother sheet is placed in a foaming furnace for foaming, the temperature of the foaming furnace is controlled to be 170-310° C., and the residence time of the cross-linked mother sheet is 0.5-7 min to obtain a magnetic high-resilience IXPE foam material for a cushioning gasket.

[0011] Preferably, the particle size of the magnetic iron oxide in step S1 is less than 1500 mesh.

[0012] Preferably, the chain length of the alkenyl acid chloride in step S2 should be between 8 and 25, and the number of double bonds of the alkenyl acid chloride should not be more than 3.

[0013] The beneficial effects of the present invention are as follows: the present application introduces silane coupling treatment of magnetic iron oxide and alkyl lignin into the polyethylene foam formula, and by selecting a suitable silane coupling agent, the iron oxide powder is modified to avoid its agglomeration while improving its compatibility with polyethylene, thereby avoiding cell rupture during the foaming process. The alkyl chain length, condensed ring structure and dosage of the alkyl lignin are adjusted to ensure that the alkyl lignin and PE can be well mixed, and to promote the uniform distribution of the alkyl lignin in the PE network; on this basis, the alkyl lignin is introduced into the polyethylene network through radiation cross-linking, the mechanical modulus of the product is improved, and a corresponding ionic cross-linking structure is formed to prepare a magnetic high-resilience IXPE foam material for a cushioning gasket.

[0014] Compared with the existing technology, the magnetic high-resilience IXPE foam material prepared in this application has the following advantages: (1) The product has high resilience, and the compression resilience (25%) is above 95%; (2) The product is magnetic, and the residual magnetic induction intensity is >0.1T; (3) When the apparent density is less than 0.1 g / cm3, the thickness is 1 mm, the tensile strength is above 1.5 MPa, and the elongation is above 200%; (4) The raw materials are abundant and inexpensive; (5) The prepared materials are widely used in the mechanical shock-absorbing buffer gasket industry. DETAILED DESCRIPTION

[0015] The following is only a preferred embodiment of the present invention, and the protection scope is not limited to this embodiment. All technical solutions under the concept of the present invention should belong to the protection scope of the present invention.

[0016] The invention introduces magnetic iron oxide and alkyl lignin as polyethylene foam functional components into the polyethylene foam material formula and compound them with low-density polyethylene, and forms a three-dimensional cross-linked network through radiation cross-linking and high-temperature foaming to prepare a magnetic high-resilience polyethylene foam material.

[0017] It should be noted that: (1) The present invention adopts the GB / T 6669 method for determining the compression permanent deformation of soft polymeric materials to determine the compression resilience (25%) of the material.

[0018] (2) The present invention adopts the wetting tension test surface tension of the sample in accordance with GB / T 14216-2008.

[0019] (3) The present invention adopts GB / T 3682-2000 for the determination of the mass flow rate and volume flow rate of thermoplastic melt to test the melt index. (4) The present invention adopts GB / T1033-1986 plastic density and relative density test method to test material density (5) The present invention adopts GB / T 3217 permanent magnetic (hard magnetic) material magnetic test method to determine the residual magnetic induction intensity of the material.

[0020] (6) The present invention adopts the method for determining the tensile strength and elongation at break of flexible foam polymer materials in GB / T 6344 to test the mechanical properties of the material. The present invention will be further described below through specific embodiments: Step 1: Synthesis of magnetic oxide powder 2000 mesh magnetic iron oxide, vinyl triethoxysilane and toluene were heated to 110°C in a mass ratio of 100:10:1000, reacted for 12 hours, and then the magnetic iron oxide powder was filtered, washed and dried.

[0021] Step 2 Synthesis of alkyl lignin Lignin with a molecular weight of 4000, dodecenoyl chloride and N,N-dimethylformamide were mixed and stirred in a mass ratio of 100:15:300, and nitrogen was passed to replace the air. Then, the mixture was heated at 130°C for 8 hours, filtered, washed with ethyl acetate and dried to obtain the corresponding alkyl lignin.

[0022] Step 3 Polyethylene foam preparation Magnetic iron oxide powder, alkyl lignin, polyethylene, POE, antioxidant, azodicarbonamide, zinc stearate, etc. are mixed uniformly in a mass ratio of 10:15:60:15:1:10:2, and then added into a single screw extruder for extrusion, and the extrusion temperature is controlled at (95-130°C), the screw speed is 15rpm, and the die temperature is 125°C to obtain a mother sheet of a certain thickness of 0.5 mm; then, the mother sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 25kGy to form a cross-linked polymerization network; finally, the cross-linked mother sheet is placed in a foaming furnace for foaming, and the temperature of the foaming furnace is controlled to be 170-310°C, and the residence time of the cross-linked mother sheet is 0.5min, so as to obtain a magnetic high-resilience IXPE foam material for a cushioning gasket. Compression resilience (50%): 96%, residual magnetic induction intensity: 0.14T, longitudinal tensile strength: 2.5 MPa, longitudinal elongation at break: 215%, transverse tensile strength: 1.8 MPa, transverse elongation at break: 260%.

[0023] Example 2-Example 6 Except that the olefinic acid chlorides are respectively changed to propylene acid chloride, octenoyl chloride, oleoyl chloride, linoleoyl chloride and linolenoyl chloride when preparing alkyl lignin in step S2, the other conditions and operations are the same as those in Example 1. The results are shown in Table 1 below.

[0024] Table 1 As shown in Table 1, when the carbon chain of olefinic acid chloride is short, it cannot form good entanglement with polyethylene and has poor performance, such as Example 2. At the same time, when the double bond content is too high, it will also cause excessive cross-linking, affecting product performance.

[0025] Example 7-Example 9 Except for the mass fraction of magnetic iron oxide powder, other conditions and operations are the same as those in Example 1. The results are shown in Table 2 below.

[0026] Table 2 It can be seen from Table 2 that when the amount of magnetic iron oxide is low, such as in Example 7, the magnetism of the product is weak, and increasing the amount will reduce the mechanical properties of the product.

[0027] Example 10-Example 12 Except for the mass parts of the alkyl lignin used, the other conditions and operations are the same as those in Example 1. The results are shown in Table 3 below.

[0028] Table 3 It can be seen from Table 3 that alkyl lignin has an important influence on the performance of the product. When alkyl lignin is not added, such as in Example 10, the compression resilience of the product is very poor.

[0029] The specific embodiments described above further illustrate the technical problems, technical solutions and beneficial effects solved by the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A magnetic high-resilience IXPE foam material for a buffer gasket, characterized in that: It consists of the following components by weight: 35-60 parts of polyethylene; 10-30 parts of alkyl lignin; 8-15 parts of magnetic iron oxide powder; 10-30 parts of elastomer; 1 to 5 parts of sensitizer; 2 to 20 parts of azodicarbonamide foaming agent; 0.5-4 parts of antioxidants; The polyethylene is low-density polyethylene, and the magnetic iron oxide powder is magnetic iron oxide powder that has been treated with silane coupling. After the components are mixed, they are added into a screw extruder for mixing and extrusion to obtain a mother sheet, and the mother sheet is cross-linked by electron radiation. After the electron radiation cross-linking is completed, the obtained material is subjected to high-temperature foaming treatment to obtain a magnetic high-resilience IXPE foam material.

2. The magnetic high-resilience IXPE foam material for a buffer gasket according to claim 1, characterized in that: The polyethylene is General low-density polyethylene with a density of 0.901~0.922g / cm3 and a melt index of 1~6 g / 10 min, Linear low-density polyethylene with a density of 0.905~0.930g / cm3 and a melt index of 0.3~5g / 10 min, One or more ultra-low density polyethylenes with a density of 0.880-0.910 g / cm3 and a melt index of 0.35 g / 10 min.

3. The magnetic high-resilience IXPE foam material for a buffer gasket according to claim 1, characterized in that: The elastomer is one or more of EPDM rubber, ethylene-octene copolymer, ethylene-hexene copolymer, ethylene-butene copolymer, ethylene-vinyl acetate copolymer, natural rubber, isobutyl rubber, styrene-butadiene rubber, styrene-butadiene block copolymer, and pentylbenzene block copolymer.

4. The magnetic high-resilience IXPE foam material for a buffer gasket according to claim 1, characterized in that: The antioxidant is Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate 1,1,3-Tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-Trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, Any one or more of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, and tert-butylhydroquinone.

5. The magnetic high-resilience IXPE foam material for a buffer gasket according to claim 1, characterized in that: The sensitizer is one or more of zinc stearate and zinc oxide.

6. The method for preparing a magnetic high-resilience IXPE foam material for a buffer gasket according to claim 1, characterized in that: The method uses magnetic iron oxide powder and alkyl lignin as reinforcing components to prepare a magnetic high-resilience polyethylene foam material, which specifically includes the following steps: S1: synthetic magnetic iron oxide powder, The magnetic iron oxide, silane coupling agent and toluene are heated to 80-120° C. in a mass ratio of 100:1-10:1000, reacted for 4-24 hours, filtered, washed and dried to obtain magnetic iron oxide powder; S2: Synthetic alkyl lignin, Lignin with a molecular weight of less than 5000, olefinic acid chloride and N,N-dimethylformamide are mixed and stirred in a mass ratio of 100:10-50:100-500, nitrogen is introduced to replace the air, and then heated at 100-150° C., reacted for 4-12 hours, filtered, washed with ethyl acetate and dried to obtain alkyl lignin; S3: preparing polyethylene foam, Magnetic iron oxide powder, alkyl lignin, polyethylene, elastomer, antioxidant, azodicarbonamide foaming agent, sensitizer, etc. are uniformly mixed in a mass ratio of 8-15:10-30:35-60:10-30:0.5-4:2-20:1-5, and then added into a single screw extruder for extrusion at an extrusion temperature of 95-130°C, a screw speed of 6-25rpm, and a die head temperature of 90-130°C to obtain a mother sheet with a certain thickness; The master sheet is passed through an electron accelerator for irradiation cross-linking, and the irradiation dose is controlled to be 5 to 50 kGy to form a cross-linked polymer network to obtain a cross-linked master sheet; The cross-linked mother sheet is placed in a foaming furnace for foaming, the temperature of the foaming furnace is controlled to be 170-310° C., and the residence time of the cross-linked mother sheet is 0.5-7 min to obtain a magnetic high-resilience IXPE foam material for a cushioning gasket.

7. The method for preparing a magnetic high-resilience IXPE foam material for a buffer gasket according to claim 6, characterized in that: The particle size of the magnetic iron oxide in step S1 is less than 1500 mesh.

8. The method for preparing a magnetic high-resilience IXPE foam material for a buffer gasket according to claim 6, characterized in that: The chain length of the alkenyl acid chloride in step S2 should be between 8 and 25, and the number of double bonds of the alkenyl acid chloride should not be more than 3.